Board Independence and Earnings Stability: A Non-linear Perspective from Indian Companies - Potharla, Srikanth; Kolpula, Suman (Copernican Journal of Finance & Accounting, 2024)
This research examines the relationship between board independence and earnings stability in Indian companies. The study focuses on the BSE-500 index constituents, which represent 4,044 firm-years from 2011 to 2022, and aims to fill gaps in the literature by providing insights into how various board characteristics affect earnings stability. The study employs a novel non-linear approach that integrates Resource Dependency Theory (RDT) and Stewardship Theory to assess the impact of board independence on earnings stability. The study uses a quadratic regression model to examine the relationship between board independence and earnings stability, with earnings stability measured using the Return on Assets Consistency Ratio (ROACR). The findings indicate an inverted U-shaped relationship between board independence and earnings stability, suggesting there is an optimal level of board independence that maximizes stability in earnings. The study also explores other factors such as asset turnover ratio, institutional ownership, leverage, promoter holdings, and firm size. This research highlights the importance of balanced board composition and provides valuable insights for policymakers and practitioners aiming to optimize corporate governance structures for sustainable firm performance.